Firm choices in the acquisition of technologies from government agencies a case study of the transfer of herbal medicines from DOST-OSIST to NMPC - Diaz, Jeremie Jan A.; Posadas, Dr. Roger (Quezon City University of the Philippines Diliman, 2013)
Firms seek innovation by acquiring external technologies. Technology acquisition is defined as the use of other companies' technologies as essential prerequisites for the long-term survival of the company (Ford & Saren, 1996). NMPC is seeking technologies from outside sources to be innovative and market growth. One of the external sources the company identified is the OSIST web portal of the DOST. It is a repository web site for firms to learn from a wide range of technologies. Under the pharmaceutical technologies category, there are 15 available technologies from the OSIST web portal. NMPC identified 4 technologies to acquire from DOST-OSIST web portal, namely : Akapulko Antifungal Lotion, Ampalaya Tablet for Type II Diabetes, Lagundi Pediatric Syrup for Asthma and Cough and Yerba Buena Analgesic Tablet. The acquisition of technologies requires a number of methods depending on factors that affect the decision process. According to Ford & Saren (1996), there are five factors to consider, namely : the firm's relative standing, category of the technology, urgency of acquisition, commitment/investment involved in the acquisition and technology life cycle position. Using the framework as criteria identifies a corresponding technology acquisition method. For this study, the technology transfer methods for external acquisition are joint venture, contracted out R&D and licensing in. Based on the questionnaire, the technology transfer methods to be used for the identified technologies from DOST-OSIST web portal are : (1) Joint venture for Akapulko Antifungal Lotion, Lagundi Pediatric Syrup for Asthma and Cough and Yerba Buena Analgesic Tablet; and (2) Licensing in for Ampalaya Tablet for Type II Diabetes. The results are then, validated by Dr. Francis Gomez, the CEO of NMPC. As the top manager of the company, Dr. Gomez is the main decision maker in technology acquisition plans of the company. Dr. Gomez sees no feasibility in implementing joint venture with the identified owner of the technology, University of the Philippines - Manila. However, Dr. Gomez agrees to obtain the license for the use of Ampalaya Tablet. According to Dr. Gomez, forming joint ventures with government agencies even an academic institution leads to more problems due to bureaucracy, low standards and research quality and prone to corruption. Based on the results of this study, using the framework of Ford & Saren (1996) to identify technology transfer methods in acquiring external technologies is not valid for NMPC as far as its engagement with government agencies is concerned. Obtaining a license is a common transfer method particularly from government agencies. However, forming joint venture with government agencies is not a feasible engagement due to arising problems on bureaucracy, low standards and research quality and corruption problems as identified by the respondent.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Herbs -- Therapeutic use; Technology transfer